2019
DOI: 10.1080/10408444.2019.1578729
|View full text |Cite
|
Sign up to set email alerts
|

Harmonized methodology to assess chronic dietary exposure to residues from compounds used as pesticide and veterinary drug

Abstract: Risk assessments for pesticide and veterinary drug residues in food are performed respectively by the Joint FAO/WHO Expert Meeting on Pesticide Residues (JMPR) and the Joint FAO/WHO Expert Committee on Food Additives (JECFA). The models used by the two Committees to assess chronic dietary exposure are based on different data and assumptions which may be confusing, particularly for risk managers, when the same compound is used to treat plants and animals. This publication details the results of combined chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…There is also concern about the presence of pesticides in the food chain, although there is still no evidence connecting pesticides to IBDs [60]. A recent study from the NutriNet French cohort found that more frequent organic food consumption decreased cancer risk [61].…”
Section: Exclusion Dietsmentioning
confidence: 99%
“…There is also concern about the presence of pesticides in the food chain, although there is still no evidence connecting pesticides to IBDs [60]. A recent study from the NutriNet French cohort found that more frequent organic food consumption decreased cancer risk [61].…”
Section: Exclusion Dietsmentioning
confidence: 99%
“…To carry out the exposure assessment and risk characterization, the model was developed using Microsoft Excel 2010 with the add‐on @Risk 5.5 software (Palisade Corporation, Newfield, New York, USA). In chronic dietary, exposure assessment is preferred to use the median of the residues in the tissues of the target species (Arcella et al., 2019). Therefore, FIP + FIP‐SO 2 concentrations are shown as median and range.…”
Section: Methodsmentioning
confidence: 99%